2022
DOI: 10.21203/rs.3.rs-1427027/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brief Overview of Dietary Intake, Gut Microbiota, Metabolic Markers and Research Opportunities in Sample of Egyptian Women

Abstract: Back ground: Metabolic syndrome (MetS) is a phenotype caused by interaction of host intrinsic factors such as genetics and gut microbiome, and extrinsic factors such as diet and lifestyle. Aim: To demonstrate the interplay of intestinal microbiota with obesity, MetS markers and some dietary ingredients among sample of Egyptian women. Methods: A cross-sectional study included 115 Egyptian women; 82 obese (59 without MetS and 23 with MetS) and 33 normal weight ones. Anthropometric assessment, 24 hours dietary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Increased Firmicutes/Bacteroidetes ratios (F/B) can lead to a variety of pathological states such as obesity and irritable bowel syndrome (IBS), [57] and it is considered to be an important marker of gut microbiota health. [58][59][60] Analysis of the relative ratio of Firmicutes to Bacteroidetes at the phylum level showed that the MG group had a significant increase of this variable compared with the other groups, while the MFG group showed a value roughly equivalent to that of the CG group.…”
Section: Analysis Of the Gut Microbiota Compositionmentioning
confidence: 99%
“…Increased Firmicutes/Bacteroidetes ratios (F/B) can lead to a variety of pathological states such as obesity and irritable bowel syndrome (IBS), [57] and it is considered to be an important marker of gut microbiota health. [58][59][60] Analysis of the relative ratio of Firmicutes to Bacteroidetes at the phylum level showed that the MG group had a significant increase of this variable compared with the other groups, while the MFG group showed a value roughly equivalent to that of the CG group.…”
Section: Analysis Of the Gut Microbiota Compositionmentioning
confidence: 99%